Digitalisation Guide Book of Basic Physics Practicum Equilibrium Material - Tanti; Kurniawan, Dwi Agus; Anggraini, Lika; Perdana, Rahmat (JTP - Jurnal Teknologi Pendidikan, 2021)
This article presents research on inquiry-based e-modules for science process skills. This lab module is made with stages of development, implementation and evaluation adopted from branch. The purpose of this study is to determine the science process skills and perceptions of Jambi University physics education students after using basic physics e-module based on science process skills with inquiry models that use 3D pageflip application software. The results show that students who have used electronic modules have a better perception of electronic modules than ordinary modules they use, this is reinforced by the presence of a significant difference between students who use e-modules and those who do not, students are more interested in using electronic modules because it is easy carried anywhere and can be used anywhere.